The Empty Fox Hole. - Van Cauteren, Philippe (Gent : HISK, 2016)
Debeer, Lydia ; Gelzis, Indrikis ; Gu, Minja ; Hernàndez, Alejandra ; Huwels, Lien ; Lobera, Almundena ; Matrokhin, Oleg ; Moraes, Pedro ; Raes, Joke ; Shust, Jura ; Tamane, Diana ; Van Boxelaere, Anne ; Wester, Wieske
The Empty Fox Hole, HISK, Gent, 18 november - 12 december 2016
boek